Diskursverweigerung und Gewalt Dimensionen der Radikalisierung des politischen Klimas in der obersteirischen Industrieregion 1927 - 1934 - Brandtner, Marina (Studien Verlag, 2011)
This book is about political conflict in the First Austrian Republic, in a region which can be aptly described as having been a focal point of social and political antagonism in the times under consideration. Its main subject, the somewhat nebulous phenomenon of political radicalism, was studied from a closer viewpoint and pinpointed in a representative selection of events. It was not only incidents of greater national significance, such as the outcome of the Schattendorf trial, the so-called Pfrimer Putsch or the deconstruction of democracy, that had contributed to the already tense atmosphere on the local front. Day to day scuffles, paramilitary parades, inflammatory speeches and street rallies triggered off a spiral of violence. This book focuses on the question of how and to what extent political parties and movements were able to influence the life and thought of so many people and made some of them become irreconcilable enemies. A glance behind the scenes of those inglorious times shall hopefully enable a far better understanding of what impact political interaction had on the region in question. After an introduction into the methodology and theory, followed by a brief summary of the political and economic situation in Austria after the First World War, the book continues with a description and history of the Upper Styrian industrial region. The major part of this study, however, deals with the origins and development of the most important regional political parties and movements and how political radicalism manifested itself in daily affairs. In this section, political leaders and other people who played a role in confrontation come to the fore and election results are presented and analysed, showing a substantial drift to the right by 1932. The growth of political radicalism during the First Republic can be seen in four phases, starting prior to 1927 and coming to a head in the 1931 Pfrimer Putsch and the uprisings of1934. According to Botz, acts of political violence were committed by individuals or groups in organised or random gatherings, demonstrations and skirmishes in guest houses and in the street. This atmosphere of unrest was aggravated further by acts of sabotage and terror carried out mainly by followers of the upcoming Nazi party. The struggle for ultimate national power can be seen as a battle between left and right ideologies against a background of national defeat, economic recession and increasing pressure exerted by certain other European states, all of which had specific interest in Austria. Finally, the issues and problems presented in this book are discussed and analysed in a conclusion. The dimensions of political radicalism are clearly defined and put into a regional context. As a consequence, the political interaction of conflicting parties, which can be traced on all social and political levels, becomes tangible. However, due to the lack of comparative regional studies, the question as to whether or not political radicalism was inherent to this particular region cannot be satisfactorily answered.